2020
DOI: 10.3174/ajnr.a6752
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Carotid Atherothrombosis and Stroke

Abstract: We present a radiology-pathology case series of 3 patients with coronavirus disease 2019 (COVID-19) with acute ischemic stroke due to fulminant carotid thrombosis overlying mild atherosclerotic plaque and propose a novel stroke mechanism: COVID-associated carotid atherothrombosis. ABBREVIATIONS: ACE2 ¼ angiotensin-converting enzyme 2; CCA ¼ common carotid artery; COVID-19 ¼ coronavirus disease 2019; RT-PCR ¼ reverse-transcriptase polymerase chain reaction; SARS-CoV-2 ¼ Severe Acute Respiratory Syndrome coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In 2 patients a thrombus in the aortic arch was also found. 2 , 18 In the 5 cases in which a CEA was performed 3 , 18 , 19 the findings were organized thrombus moderately adherent to a soft CCA wall. Esenwa et al 18 analyzed the CCA wall in 3 cases and all of them found intima inflammatory infiltrates in the wall adherent to the thrombus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2 patients a thrombus in the aortic arch was also found. 2 , 18 In the 5 cases in which a CEA was performed 3 , 18 , 19 the findings were organized thrombus moderately adherent to a soft CCA wall. Esenwa et al 18 analyzed the CCA wall in 3 cases and all of them found intima inflammatory infiltrates in the wall adherent to the thrombus.…”
Section: Discussionmentioning
confidence: 97%
“… 2 , 18 In the 5 cases in which a CEA was performed 3 , 18 , 19 the findings were organized thrombus moderately adherent to a soft CCA wall. Esenwa et al 18 analyzed the CCA wall in 3 cases and all of them found intima inflammatory infiltrates in the wall adherent to the thrombus. The authors suggest that, in patients with COVID-19, areas of mild carotid atherosclerosis may be particularly prone to thrombus formation because of the unique combination of endothelitis and COVID-19-associated coagulopathy.…”
Section: Discussionmentioning
confidence: 97%
“…Indes et al [ 178 ] also reported an elevation of risk for acute arterial thromboembolic complications in patients with COVID-19 infection. Esenwa et al [ 179 ] presented a radiology-pathology case series of three COVID-19 patients and reported that a disproportionately high intra-luminal thrombus in the carotid artery showing mild-to-moderate atherosclerotic disease with intimal thickening and plaque calcification. Mohamud et al [ 180 ] presented a case study of six COVID-19 patients that had atherosclerotic plaque vulnerability and the development of thrombotic events.…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During mentioning
confidence: 99%
“…The events occurred mostly in the second week from onset of symptoms (8.5 ± 5.8 days) [ 61 ]. Several case report series evidenced massive carotid artery thrombosis in COVID-19 patients, with relatively low extent of atherosclerotic plaques and high levels of inflammatory biomarkers highlighting the impact of systemic inflammation and endothelial dysfunction on atherosclerotic plaques of any localization in the vascular system [ 62 , 63 , 64 ]. In a single center study, which included 388 COVID-19 patients from Milan, Italy, the authors reported a 7.7% ( n = 28) cumulative incidence of arterial and venous thrombotic events, with higher rates of events in ICU patients compared to general ward (16.7%, 95%CI 8.7%–29.6% vs. 6.4%, 95%CI 4.2%–9.6%), with most frequent clinical presentation of venous thromboembolism (8.3% in ICU vs. 3.8% on general ward).…”
Section: Covid-19—a Trigger For Systemic Thrombosismentioning
confidence: 99%